2018
DOI: 10.3389/fpls.2018.01278
|View full text |Cite
|
Sign up to set email alerts
|

Aphid Colonization Affects Potato Root Exudate Composition and the Hatching of a Soil Borne Pathogen

Abstract: Plants suffer multiple, simultaneous biotic threats from both above and below ground. These pests and/or pathogens are commonly studied on an individual basis and the effects of above-ground pests on below-ground pathogens are poorly defined. Root exudates from potato plants (Solanum tuberosum L.) were analyzed to characterize the top-down plant-mediated interactions between a phloem-sucking herbivore (Myzus persicae) and a sedentary, endoparasitic nematode (Globodera pallida). Increasing inocula of the aphid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 63 publications
(84 reference statements)
0
20
0
Order By: Relevance
“…However, several sugar beet genotypes showed tolerance to beet root aphid [ 86 ]. Reductions of the root mass of carrot and potato plants due to the feeding of black bean aphid and green peach aphid, respectively, were reported by Ɓuczak et al [ 87 ] and Hoysted et al [ 88 ], respectively. Ɓuczak [ 52 ] further reported that black bean aphid did not always cause a decrease in the yield of sugar beet roots, which depended largely on the size of the aphid colonies.…”
Section: Discussionmentioning
confidence: 89%
“…However, several sugar beet genotypes showed tolerance to beet root aphid [ 86 ]. Reductions of the root mass of carrot and potato plants due to the feeding of black bean aphid and green peach aphid, respectively, were reported by Ɓuczak et al [ 87 ] and Hoysted et al [ 88 ], respectively. Ɓuczak [ 52 ] further reported that black bean aphid did not always cause a decrease in the yield of sugar beet roots, which depended largely on the size of the aphid colonies.…”
Section: Discussionmentioning
confidence: 89%
“…The herbivory-driven effect on the bacterial community composition of the roots and rhizosphere could be driven by changes in plant physiology (e.g. defence activation, carbon metabolism) and root exudation due to aphid feeding activity (ZĂŒst and Agrawal, 2016; Hoysted et al , 2018). Herbivory has been shown to alter the types of organic compounds released at the root surface leading to changes in the composition of rhizosphere microbial communities (Lareen et al , 2016; Hu et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient flows below-ground were not measured in the current study, but aphids can affect below-ground respiration depending on plant growth stage, potentially due to alterations in C availability to soil microbes (VestergĂ„rd et al, 2004). Aphids can also alter the profiles of compounds, released from plant roots (Hoysted et al, 2018) and can also change the profiles of sugars found in AMF hyphae sharing the same host plant (Cabral et al, 2018). Moreover, aphids excrete honeydew as a result of their C rich diet of phloem sap which can be utilized as a C source by soil microbiota, thus shaping community structure and biomass (Katayama et al, 2014; Milcu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%